(untitled) (Sains Humanika, 2018)
Based on the government’s aspiration towards realizing the 21st century education (PA-21), the Ministry of Education (MOE) has listed 10 subthemes of the three skills that need to be mastered in teaching and learning namely learning and innovation skills, media and information technology skills, as well as life skills and careers. Institut Aminuddin Baki (IAB) took up the challenge of the MOE’s aspiration by listing eight elements of the PA-21 based on the 21st century learning style of the US National Educator Association (NEA) such as critical, communication, collaborative and creativity. This article is an overview of 14 local studies findings that were published in journals and educational research proceedings in Malaysia from 2000 to 2017. All of these articles have discussed the feasibility of PA-21 at the public schools and universities. Findings from these studies show that local research more focuses on two domains of skills namely creativity and communication i.e. the use of information technology in teaching and learning. This review is empirically prove that teachers and students were able to implement PA-21 skills although the level of implementation was still at the early stage with the most basic method of use. However, the implementation of PA-21 from the perspectives and functions of MOE as the policy makers was not addressed in 14 analyzed articles.